Native Canadian Education Past and Present - Nemes, Tamásné (2008)
“American Indian and Native Canadian communities need skilled members if they are to survive and thrive,” asserts Keith James (James 2001). That’s true for all minority groups all around the world. At the same time minority groups have their education problems in each country. When I started to learn about First Nations education in Canada I only knew that Canada is one of the best-working multicultural countries in the world that has educational projects for all means of education and all groups of students. I have been eager to know how Aboriginal education projects help students fight difficulties. As some experts, for instance Sabrina E. Redwing Saunders and Susan M. Hill state in their study, for a long time Aboriginal education was only a “tool” of dealing with the “Indian Problem” (Saunders and Hill 2007). They state “For centuries Canadian First Nations education has been a substandard, abusive means of dealing with the “Indian Problem”. We cannot neglect these centuries if we want to see the sequence of development that characterizes the Aboriginal education in Canada. angol nyelv és irodalom (levelező) egyetemi